Search for exclusive Higgs and Z boson decays to ϕγ and ργ with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Jongmanns, Jan; et al. (Journal of high energy physics, 2018)
A search for the exclusive decays of the Higgs and Z bosons to a φ or ρ meson and a photon is performed with a pp collision data sample corresponding to an integrated luminosity of up to 35.6 fb−1 collected at √s = 13 TeV with the ATLAS detector at the CERN Large Hadron Collider. These decays have been suggested as a probe of the Higgs boson couplings to light quarks. No significant excess of events is observed above the background, as expected from the Standard Model. Upper limits at 95% confidence level were obtained on the branching fractions of the Higgs boson decays to φγ and ργ of 4.8 × 10−4 and 8.8 × 10−4, respectively. The corresponding 95% confidence level upper limits for the Z boson decays are 0.9 × 10−6 and 25 × 10−6 for φγ and ργ, respectively.